Tindak Tutur Ilokusi Pada Wacana Pojok Surat Kabar Kompas Edisi November 2015 Diimplementasikan Dalam Pelajaran Bahasa Indonesia Sma/Smk Kelas X - Marfu'ah, Yohana Dwi, Dra. Atiqa Sabardila, M. Hum (2016)
This research paper aims: (1) to describe analysis ilokusi speech act in the corner Kompas edition of November 2015, and (2) to explain the form of implementation in Indonesian language teaching SMA/SMK class X. The result in this research is the form of ilokusi speech act that located in the Wacana Pojok there are 92 data. Based on the results of the classification of that has done there are five the classifications are asertif speech act as much as 49 data, directive speec h act as much as 17 data, expressive speech act as much as 16 data, komisif speech act as much as 6 data, and declaration speech act as much as 3 data. Based on the analysis that has done of asertif speech acts found the reported, complained, explained, suggested opinions, bragged, and proposed. Directive speech act found the form of rules, giving advice, demanding, and pleaded. Expressive speech act found the form of inveigh. Komisif speech act found the form of offer and promise. Declaration speech act found the form of expelled. The result of discussion ilokusi speech act for Wacana Pojok of newspaper Kompas related with Indonesian language teaching in the senior high school (SMA) which is exist in the syllabus curriculum 2013 with Core Competence 4, and Basic Competence 4.2 ( producing text anecdotes that coherence in accordance with the characteristics of the text will be made, both orally or written). The results of research already be translated researcher that will be implemented in Indonesian language teaching related to the material text anecdote. Implementation carried out to be referrs of the preparation RPP that includes measures of learning in order to the students can reach indicator. Keywords: Speech act, ilokusi speech act, implementation.